First record of Aspergillus flavus as a fungal pathogen of reduviid predator, Rhynocoris marginatus (Fab.) (Hemiptera: Reduviidae) - Sahayaraj, Kitherian (2012)
An entomopathogenic fungus, Aspergillus flavus Raper and Fennell is recorded as a pathogen of reduviid predator, Rhynocoris marginatus (Fab.) (Hemiptera: Reduviidae) in natural agro-ecosystems of Tirunelveli District, Tamil Nadu for the first time. Primeiro registro de Aspergillus flavus como patôgeno de reduviídeo predador  Rhynocoris marginatus (Hemiptera: Reduviidae) Resumo.  O fungo entomófago, Aspergillus flavus   Raper and Fennell é registrado como um patógeno do reduviídeo predador   Rhynocoris marginatus (Fab.) (Hemiptera: Reduviidae), em agroecossistema natural  do distrito de Tirunelveli, Tamil Nadu pela primeira vez.